Managing Your Classroom - Dixie, Gererd (London Continuum, 2007)
Teachers often find that the hardest part of their job is controlling children's behaviour. The author gives practical advice not only on how to eliminate unruly behaviour but also on how to entertain pupils
Keywords: Classroom management